Development of ethnoscience-based pbl-networked learning tools to improve students' understanding of entrepreneurship concepts and interests - Agustia, Mela; Murni, Pinta; Ernawati, M. Dwi Wiwik (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This study aims to (1) produce learning tools for the PBL-Networked model based on ethnoscience that is appropriate according to learning design experts and material experts and practical according to practitioners and (2) to find out the effectiveness of the ethnoscience-based PBL-Networked model learning tool for understanding concepts and interest in entrepreneurship in class VII junior high school students. This research is a development research that adapts the Dick & Carey. The data collection used validation questionnaires, practicality questionnaires, readability questionnaires, interest questionnaires, student entrepreneurship, and concept understanding tests. Data analysis used quantitative descriptive statistics, N-gain. The results of this development research are: (1) Ethnoscience-based PBL-Networked learning tools are suitable for use based on feasibility assessments by experts considered very good for all aspects assessed (learning materials and design), the practicality of using the tools from the teacher is considered very practical, and students' readability is also considered very good, (2) Ethnoscience-based PBL-Networked model learning tools are practical in significantly increasing students' understanding of concepts and interest in entrepreneurship. That is shown by the N-Gain values of 0.73 and 0.39, categorized into firm and robust effect sizes.